Mucoepidermoid carcinoma of the hard palate: A case report (Indian Journal of Case Reports, 2019)
Mucoepidermoid Carcinoma is an epithelial salivary gland tumor which usually occurs in younger patients and females. The following case report deals with a case of mucoepidermoid carcinoma in a 38-year-old male patient who reported with a chief complaint of swelling in the palatal region for 1 year. At first, it was diagnosed as a benign minor salivary gland tumor of the palate. Upon incisional biopsy, an impression was made according to the features present. Complete excision of the lesion was done which was then diagnosed as mucoepidermoid carcinoma. The conflict between whether the lesion was a benign minor salivary gland tumor of the palate or a malignant counterpart, was resolved and confirmed after excisional biopsy.The article focuses on various diagnostic aspects of this tumor and its surgical management.